The Effect of Giving Papaya & Honey (Carica Papaya L and Apis) Juice on Increasing the Production of Breast Milk - Yulli Fety (Eduvest - Journal of Universal Studies, 2022)
Interviews conducted by researchers on midwives and 10 postpartum mothers at the Ranomeeto Health Center, the midwife said that in January, February, March 2020 there were 51 babies but only 15 babies were given exclusive breastfeeding due to the lack of milk production in post partum mothers in the Ranomeeto Health Center area so that some mothers giving formula milk from the time of the newborn with the reason that breast milk has not come out after giving birth, this study aims to determine the effect of giving papaya leaf juice and honey to increase milk production in nursing mothers in the working area of ​​the Ranomeeto Health Center, South Konawe Regency. This study uses quantitative (analytic) research methods using a quasi-experimental design. Quasi experimental. The total population of 51 respondents and the number of samples of 21 respondents. This sampling was taken using purposive sampling technique. The results of statistical tests using Shapiro Wilk's statistics show the P Value is 0.000 so it can be concluded that there is an effect of giving papaya leaf juice and honey on increasing breast milk production for breastfeeding mothers in the Ranomeeto Health Center area, South Konawe Regency. So it is suggested to the Puskesmas to provide recommendations to mothers who are about to give birth and breastfeeding to use papaya leaf juice and honey to support smooth breastfeeding. For breastfeeding mothers, use papaya leaf juice to support smooth breastfeeding.